Accuracy of two devices and three different calculation methods for predicting residual astigmatism after intraocular lens implantation. Issue 2 (2nd April 2020) - Bicknell, Kendall; Helpert, Christopher; Dwyer, Kourtney; McKnight, Brett; Singh, Sonali; Fulcher, Samuel; Fung, Derrick
Abstract: This study examined how different methods of biometric measurement, types of intraocular lens calculation, and levels of surgeon experience affected predicted postoperative astigmatism with toric intraocular lens implantation. The error in predicted residual astigmatism was determined using the IOL Master 500 and Lenstar LS 900 devices and was calculated by the Alcon toric calculator, Alcon toric calculator with Baylor nomogram, and Barrett toric calculator. Results were reviewed from 147 eyes of 125 patients. Of the three calculations, the Barrett toric calculator had the lowest mean absolute error in predicted residual astigmatism ( P  < 0.0001). The mean absolute errors of the IOL Master 500 and the Lenstar LS 900 were not significantly different when compared using three different calculation methods ( P =  0.54). The mean absolute error was significantly lower ( P =  0.049) for ophthalmology staff than for ophthalmology residents when calculation methods were considered. In conclusion, the calculation method used for IOL selection in cataract surgery significantly affects the accuracy of both staff and residents.